2014
DOI: 10.3126/njh.v11i1.10976
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Profile of Patients in Dhulikhel Hospital, A Medical College Hospital in Nepal

Abstract: Background and Aim : Echocardiograph is an important diagnostic tool to evaluate cardiac disease and is indispensible for management. So it is important to know the spectrum of cardiac abnormalities that can be detected by echocardiograph and the frequency of these findings may vary depending on where the echocardiogram is performed. Aim of this study was to find out the spectrum of echocardiographic finding in different age group in a medical college hospital. Methods and materials : A retrospective observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…8 The echocardiographic result revealed that 5(10%) had hypertensive heart disease, which is lower than the general population, and 32 (64%) participants had normal echo findings, which is higher than the general population of Nepal. 7 The prevalence of mild mitral regurgitation (22%) is lower than that when compared to the general Chinese population. 9 CONCLUSION This is the first reported observational study so far, we know among the traffic police personnel in Nepal.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…8 The echocardiographic result revealed that 5(10%) had hypertensive heart disease, which is lower than the general population, and 32 (64%) participants had normal echo findings, which is higher than the general population of Nepal. 7 The prevalence of mild mitral regurgitation (22%) is lower than that when compared to the general Chinese population. 9 CONCLUSION This is the first reported observational study so far, we know among the traffic police personnel in Nepal.…”
Section: Discussionmentioning
confidence: 96%
“…3 Streptococcal sore throat that causes rheumatic heart disease, complications from tuberculosis, parasite infestation that causes pericardial illnesses, and non-communicable diseases like hypertension and ischemic IHD continue to be a significant burden in developing nations like Nepal. 6,7 Therefore, we carried out this cross-sectional study to examine the impact of these conditions in highly demanding jobs like traffic police compared to a typical healthy population. In this study, we inquired about hypertension history, performed auscultation, and conducted echocardiography to determine whether any structural or valvular heart disease was present in these participants.…”
Section: Discussionmentioning
confidence: 99%
“…BP Koirala Institute of Health Sciences (BPKIHS), Dharan; Manipal medical college, Pokhara; Chitwan Medical College, Chitwan; Amda Hospital, Butwal and Kathmandu university Teaching Hospital, Dhulikhel, are some of the centers outside Kathmandu that perform echocardiography in suspected cases before referring patients for the definite diagnosis and management. [17][18][19] Currently, open heart surgery is primarily being done in SGNHC and Manmohan Cardiothoracic Vascular and Transplant Centre and sporadically in Norvic Hospital, Greencity Hospital, Nepal Mediciti Hospital, Human Organ Transplant Centre all within Kathmandu along with Kathmandu University Teaching Hospital, Dhulikhel and College of Medical Sciences, Chitwan.…”
Section: Poonam Sharmamentioning
confidence: 99%